Assessing physical activity, nutrient intake and obesity in middle-aged adults in Akuse, Lower Manya Krobo, Ghana - David Adjatey Nyakotey; Alberta Seyram Ananga; Charles Apprey (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this paper is to assess physical activity and nutrient intake and their association with obesity in apparently healthy middle-aged adults in Akuse, a rural community in the Eastern region of Ghana. Design/methodology/approach - This cross-sectional study assessed demography and anthropometry, nutrient intakes using a 3-day repeated 24 h dietary recall and physical activity using the global physical activity questionnaire (GPAQ). Data were entered into Microsoft excel and analyzed with SPSS version 25. Findings - There were 118 respondents (55 males, 46.6% and 63 females, 53.4%) in the study with mean age of 45.62 ± 6.88 years. About 90% of respondents were physically active based on WHO physical activity recommendation. Prevalence of overweight/obesity was higher among inactive participants compared to active participants and sitting/reclining hours was significantly (p-value = 0.042) associated positively with BMI after a bivariate correlation analysis, suggesting that physical activity plays a role in obesity. About one in five respondents were obese. Mean energy intake exceeded RDA for females. Sodium intake far exceeded RDA for both males and females, putting the population at potential risk of hypertension. Practical implications - This study demonstrates the need for intensifying health education and other obesity prevention interventions to curb the rising obesity prevalence in rural communities. Originality/value - The study revealed that overweight/ obesity in this rural community is higher than previously reported for rural Ghana.